2005
DOI: 10.1002/jcp.20278
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of C/EBPβ and δ are upregulated by dexamethasone in skeletal muscle

Abstract: The influence of glucocorticoids on the expression and activity of the transcription factors CCAAT/enhancer binding protein (C/EBP)beta and delta in skeletal muscle was examined by treating rats or cultured L6 myotubes with dexamethasone. Treatment of rats with 10 mg/kg of dexamethasone resulted in increased C/EBPbeta and delta DNA binding activity in the extensor digitorum longus muscle as determined by electrophoretic mobility shift assay (EMSA) and supershift analysis. A similar response was noticed in dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 35 publications
(52 reference statements)
9
101
1
Order By: Relevance
“…Several studies demonstrated that interaction of GR with other transcription factors could provide an alternative pathway for GC actions (Hayashi et al 2004, Smoak & Cidlowski 2004. GCs have been found to induce C/EBPa or C/EBPb expression in a number of tissues or cells (Zilberfarb et al 2001, Hernandez et al 2003, Yang et al 2005a. Furthermore, interaction of C/EBP a and GR has been found to regulate cell proliferation (Rudiger et al 2002, Roth et al 2004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that interaction of GR with other transcription factors could provide an alternative pathway for GC actions (Hayashi et al 2004, Smoak & Cidlowski 2004. GCs have been found to induce C/EBPa or C/EBPb expression in a number of tissues or cells (Zilberfarb et al 2001, Hernandez et al 2003, Yang et al 2005a. Furthermore, interaction of C/EBP a and GR has been found to regulate cell proliferation (Rudiger et al 2002, Roth et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not know whether the putative GRE and CCAAT boxes are truly involved in the regulation of 11b-HSD1 expression by GCs. C/EBPs have been reported to be closely related to the actions of GCs in a number of tissues (Rudiger et al 2002, Roth et al 2004, Yang et al 2005a,b, Woltje et al 2006. Although C/EBPs have been shown to be involved in basal expression of human or mouse 11b-HSD1 gene transcription (Williams et al 2000, Gout et al 2006, it is not known whether C/EBPs play any roles in the regulation of 11b-HSD expression by GCs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, p300 protein levels and activity are increased, in a time-and dosedependent manner, in dexamethasone-treated myotubes (Yang et al 2005). Additionally, dexamethasone increases protein-protein interaction between p300 and C/EBPb, which increases the transcription activity of C/EBPb by acetylation (Yang et al 2005). This interaction is particularly important since C/EBPb may regulate multiple genes in the UPS pathway (Penner et al 2002).…”
Section: P300-c/ebpbmentioning
confidence: 99%
“…p38 MAPK has been suggested to play a critical role in differentiation and stresses (26,27). Thus, we GSM155934 GSM155958 GSM155955 GSM155945 GSM155960 GSM155959 GSM155937 GSM155984 GSM155982 GSM155981 GSM155939 GSM155929 GSM155931 GSM155952 GSM155977 GSM155951 GSM155967 GSM155938 GSM155965 GSM155985 GSM155968 GSM155966 GSM155921 GSM155922 GSM155923 GSM155920 GSM155969 GSM155930 GSM155975 GSM155935 GSM155970 GSM155948 GSM155988 GSM155956 GSM155989 GSM155947 GSM155993 GSM155961 GSM155932 GSM155933 GSM155991 GSM155987 GSM155919 GSM155926 GSM155924 GSM155927 GSM155976 GSM155980 GSM155979 GSM155925 GSM155978 GSM155972 GSM155964 GSM155928 GSM155971 GSM155973 GSM155974 GSM155940 GSM155944 GSM155941 GSM155983 GSM155963 GSM155946 GSM155943 GSM155949 GSM155950 GSM155992 GSM155990 GSM155942 GSM155954 GSM155936 GSM155986 GSM155953 GSM155962 assessed whether CEBPD is responsive to anticancer drugs that are known to activate p38 MAPK, including cisplatin (28), paclitaxel (29), 5-fluorouracil (30), bortezomib (31), and dexamethasone (32) and those that affect epigenetic regulation, such as 5-AzadC (33) or induce differentiation, such as retinoic acid (34). Western blotting analyses showed that they all induce CEBPD expression ( Supplementary Fig.…”
Section: Cebpd Expression Is Responsive To Hmdb and Participates In Hmentioning
confidence: 99%